Acute and Chronic Effects of Exercise on Continuous Glucose Monitoring Outcomes in Type 2 Diabetes: A Meta-Analysis - Munan, Matthew; Oliveira, Camila L. P.; Marcotte-Chénard, Alexis; Rees, Jordan L.; Prado, Carla M.; Riesco, Eléonor; Boulé, Normand G. (Frontiers in Endocrinology, 2020)
Objective. To examine the acute and chronic effects of structured exercise on glucose outcomes assessed by continuous glucose monitors in adults with type 2 diabetes. Methods. PubMed, Medline, EMBASE were searched up to January 2020 to identify studies prescribing structured exercise interventions with continuous glucose monitoring outcomes in adults with type 2 diabetes. Randomized controlled trials, crossover trials and studies with pre-post designs were eligible. Short-term studies were defined as having exercise interventions lasting <2 weeks. Longer-term studies were defined as >2 weeks. Results. A total of 28 studies were included. Of these, 23 studies were short-term exercise interventions. For all short-term studies, the same participants completed a control condition as well as at least one exercise condition. Compared to the control condition, exercise decreased the primary outcome of mean 24-hour glucose concentrations in short-term studies (-0.5 mmol/L, [-0.7, -0.3]; p<0.001). In longer-term studies, mean 24-hour glucose was not significantly reduced compared to control (-0.9 mmol/L [-2.2, 0.3], p=0.14) but was reduced compared to pre-exercise values (-0.5 mmol/L, [-0.7 to -0.2] p<0.001). The amount of time spent in hyperglycemia and indices of glycemic variability, but not fasting glucose, also improved following short-term exercise. Among the shorter-term studies, subgroup and regression analyses suggested that the timing of exercise and sex of participants explained some of the heterogeneity among trials. Conclusion. Both acute and chronic exercise can improve 24-hour glucose profiles in adults with type 2 diabetes. The timing of exercise and sex of participants are among the factors that may explain part of the heterogeneity in acute glycemic improvements following exercise.